2009
DOI: 10.1159/000204103
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Expression of TFF and Related Genes During Postnatal Development in a Piglet Probiotic Trial

Abstract: Trefoil factor family (TFF) peptides provide protective and reparative effects by enhancing epithelial integrity and promoting mucosal restitution. TFF peptide expression is induced after mucosal damage. These processes are of central physiological relevance during the postnatal intestinal development and are strongly influenced during the weaning period. In piglets, weaning at early maturation stages frequently causes mucosal inflammation. The aim of this study was to evaluate postnatal intestinal TFF express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 69 publications
0
32
1
Order By: Relevance
“…Our detection of EGFR transcript from 0 to 49 days of age was consistent with this report. However, no postnatal change on relative EGFR expression was observed, which is inconsistent with a previous report by Scholven et al (2009) showing a decrease between 1 week of age and post weaning (Scholven et al, 2009). It is not known if pig breed differences could account for this discrepancy.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our detection of EGFR transcript from 0 to 49 days of age was consistent with this report. However, no postnatal change on relative EGFR expression was observed, which is inconsistent with a previous report by Scholven et al (2009) showing a decrease between 1 week of age and post weaning (Scholven et al, 2009). It is not known if pig breed differences could account for this discrepancy.…”
Section: Discussioncontrasting
confidence: 98%
“…These receptors play a role in determining the architecture of the intestine, the composition and proliferation of intestinal cells, and the presence of specific transporters on the brush border membrane (Pluske et al, 1997). Previous studies have revealed that intestinal EGFR, and GLP2R expression is stage dependent during neonatal development (Petersen et al, 2003;Scholven et al, 2009), though the expression patterns of SGLT1, GLUT2, and IGF-1R during this important period, and the influence of weaning on their expression, is unclear. Weaning is one of the most stressful stages in piglet development.…”
Section: Introductionmentioning
confidence: 99%
“…While both gene products play protective roles during gut inflammatory conditions, at sites of epithelial damage [18,29-34] and during postnatal development [35,36], Muc2, unlike Tff3, polymerizes into a protective gel-like structure [1]. Based on the obtained results, it is however not possible to determine whether there is a connection between this difference in functionality and the corresponding gene regulation.…”
Section: Resultsmentioning
confidence: 99%
“…After incubation, cells were washed with PBS, lysed with RNA Lysis Buffer (miRVana Isolation Kit, Life Technologies) and total RNA was isolated according to the manufacturer's instruction. cDNA was synthesized by reverse-transcription as previously described (Scholven et al, 2009). RT-qPCR arrays were used to quantify mRNA expression of IL-1␣, IL-1ß, IL-6, IL-8, IL-10, IL-12␣, IL-12ß, TNF␣ and iNOS as well as caspase 8.…”
Section: Cell Culturementioning
confidence: 99%